Crohn’s disease and smoking: a review of the effects of the latter on inflammatory markers and gene expression - Hasan, Bassam; Al-Saigh, Rafal J.; Al-Humadi, Hussam W. (Pharmakeftiki, 2025)
Crohn’s disease (CD), a chronic form of inflammatory bowel disease, affects the gastrointestinal tract and is characterized by a multifactorial aetiology involving both genetic predisposition and environmental influences. Among environmental modifiers, cigarette smoking plays a pivotal role in exacerbating the progression and severity of CD. Individuals with CD who smoke exhibit a heightened risk of disease flare-ups, increased surgical intervention rates, and diminished responsiveness to pharmacological therapies. Smoking intensifies intestinal inflammation by elevating key biomarkers, including C-reactive protein, erythrocyte sedimentation rate, and faecal calprotectin, while simultaneously dysregulating pro-inflammatory cytokines such as tumor necrosis factor-alpha, interleukin-6, interleukin-1 beta, and interleukin-17. Furthermore, smoking alters gene expression by upregulating cytokine and matrix metalloproteinase pathways, and downregulating tight junction proteins essential for maintaining intestinal epithelial barrier integrity. These molecular disruptions compromise epithelial cohesion, exacerbate mucosal injury, and sustain chronic inflammation. Epigenetic modifications – most notably DNA methylation – further contribute to immune dysregulation in smokers with CD. Notably, smoking cessation has been associated with downregulation of pro-inflammatory gene expression and attenuation of disease activity, underscoring its therapeutic relevance in CD management. A deeper understanding of the mechanisms by which smoking modulates inflammatory biomarkers and gene expression may inform the development of targeted interventions aimed at improving clinical outcomes in patients with CD.